Parental Smartphone Addiction and Child Behavioral Problems: The Mediating Role of Parenting Quality - Acar, Zeynep; Maisarah, Syarifah (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the direct and indirect effects of parental smartphone addiction on child behavioral problems, with parenting quality as a mediating variable.Methods and Materials: A descriptive correlational design was employed with a sample of 410 parents from Malaysia, determined according to the Morgan and Krejcie sample size table. Participants were recruited through schools and community centers and completed standardized measures assessing smartphone addiction, parenting quality, and child behavioral problems. Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlations, and AMOS-21 for structural equation modeling (SEM). Model fit indices, including χ²/df, GFI, AGFI, CFI, TLI, and RMSEA, were used to assess model adequacy.Findings: Descriptive statistics revealed moderate levels of parental smartphone addiction (M = 32.47, SD = 6.81), relatively high parenting quality (M = 74.26, SD = 9.54), and mild to moderate child behavioral problems (M = 18.63, SD = 5.72). Correlation analyses showed that parental smartphone addiction was positively correlated with child behavioral problems (r = .36, p < .001) and negatively correlated with parenting quality (r = –.41, p < .001). Parenting quality was negatively correlated with child behavioral problems (r = –.44, p < .001). SEM confirmed partial mediation: parental smartphone addiction negatively predicted parenting quality (β = –.39, p < .001), which in turn negatively predicted child behavioral problems (β = –.41, p < .001). The direct path from parental smartphone addiction to child behavioral problems remained significant (β = .25, p = .001), while the indirect effect through parenting quality was also significant (β = .16, p < .001).Conclusion: The study highlights that parental smartphone addiction increases child behavioral problems both directly and indirectly through reduced parenting quality. Interventions should target reducing parental smartphone addiction and enhancing parenting practices to safeguard children’s behavioral health.